Study on activity of LRR-RLK VIII promoter driven arsenic tolerance in Arabidopsis model plant - Quỳnh, Nguyễn Thị Thúy; Hoàng, Nguyễn Huy; Hoang, Hao Jen (Vietnam Journal of Biotechnology, 2016)
The Leucine-rich repeat receptor-like kinase (LRR-RLK), that is a receptor-like kinase consists of leucine rich repeat fragments, plays an important role in the plant growth and development as well as enhancing resistance ability against environmental stress factors. LRR-RLR promoter has been studied to increasing gene expression during stress conditions the stress conditions with salt, paraquat… However, no report has been studied on activity of LRR-RLK promoter in Arsenic (As) stress. Arabidopsis is a genome sequenced-model plant and has been widely used in the studies of important traits. In this study, LRR-RLK promoter was isolated from Arabidopsis, and constructed in plant expression vector pCAMBIA1304. In which, LRR-RLK VIII promoter drives the activity of GUS (beta-glucuronidase) gene. The functional regions of the LRR-RLK VIII promoter were determined and exposed some important regulatory elements such as W-box and ABRE using the database of Cis-acting Data Plan Regulatory DNA Elements (PLACE). Using the histochemical staining hypocotyls of T1 transgenic plant with X-gluc subtrate indicated that LRR-RLK VIII promoter driven activity of GUS gene is tissue-specific in tissue vessel and hypocotyls of T1 during As stress. The increase expression of LRR-RLK VIII gene in transgenic leaves under As stress compare to control ones were also observed by RT-PCR technique.